Patient Satisfaction with Prolanis Services at Pulau Panggung Health Center - Rahmatullah, Rahmatullah; Hardono, Hardono; Yunina Elasari, Yunina Elasari (Jurnal Kesehatan, 2025)
Hypertension is one of the most common non-communicable diseases (NCDs) whose prevalence continues to increase and has become a leading cause of death in Indonesia. To address this issue, the government, through BPJS Kesehatan, launched the Chronic Disease Management Program (Prolanis), which is implemented in first-level health facilities, such as health centers. The success of this program depends greatly on patient satisfaction with the services provided. This study aims to identify factors associated with the satisfaction of patients with hypertension who use Prolanis services at the Pulau Panggung Health Center. A quantitative approach with a cross-sectional design was applied, involving 131 hypertensive patients registered as Prolanis participants. Data were collected using a structured questionnaire that referenced the five dimensions of service quality outlined in the SERVQUAL model: reliability, responsiveness, assurance, empathy, and tangibles. Data were analyzed using the chi-square test to examine the relationship between service quality dimensions and patient satisfaction. The findings revealed that all five dimensions of service quality had a significant association with patient satisfaction (p≤0.05). Among them, the tangible evidence dimension was identified as the most dominant factor influencing satisfaction. In conclusion, Prolanis' service quality plays a crucial role in determining patient satisfaction. Therefore, improving the quality of services, particularly in tangible aspects such as facility cleanliness, comfort, availability of medical equipment, completeness of infrastructure, and the professional appearance of healthcare workers, is expected to enhance the effectiveness of Prolanis implementation at health centers.